PENGARUH KARAKTERISTIK DAN PERSEPSI TERHADAP TINGKAT PARTISIPASI ANGGOTA DALAM KELOMPOK MASYARAKAT PENGAWAS (POKMASWAS) SUMBER DAYA KELAUTAN DAN PERIKANAN - Yuliana, Ernik; Winata, Adi (Bumi Lestari; Vol 12 No 2 (2012), 2012)
This article is objected to identify the member’s participation level on Pokmaswas and the factor’s were be influence. Research design was explanatory research design. Data were collected by data using survey method. The population of study was Pokmaswas’s member in Sukabumi, which is 160 people. Samples are taken randomly from each Pokmaswas, numbering 5-6 people, so the number of samples is 50 people. Data were analyzed with descriptive and multiple regression. The results showed that members of Pokmaswas be in the range of mid-age adults (36-50 years), junior high and high school level education, most are public figures, and have experience of being a member Pokmaswas more than 5 years. Characteristics Pokmaswas members who have a significant effect on the perception Pokmaswas members, is the level of education and experience of being a member Pokmaswas. The participation rate in the reporting of violations Pokmaswas member in writing and in capturing the perpetrators of violations is significantly influenced by the perception of the adequacy of Pokmaswas member. Based on research results, some suggestions can be given is to increase members' experience in running the Pokmaswas Pokmaswas, especially for members Pokmaswas derived from fishing.
Keywords: participation of Pokmaswas’s member; marine resources; fisheries resources; Pokmaswas